Collaborative health literacy development: a World Health Organization workplace health promotion approach to address tobacco use - Duxbury, Theodore Orlando (Rhodes University, Faculty of Pharmacy, Pharmacy, 2019)
Background: Non-Communicable Diseases (NCDs) are a major global public health threat and tobacco use in particular is the leading cause of preventable illness and mortality globally. Furthermore, vulnerable and socially disadvantaged people get sicker and die sooner, especially because they are at higher risk of being exposed to harmful products such as tobacco and have limited access to health services. Tobacco use also has a major impact on the workplace, adversely affecting work productivity and increasing absenteeism. Both the living and work environments, therefore, play an important role in contributing towards the NCD epidemic. Demographics, culture, behaviour change reluctance and health literacy are all factors which exacerbate tobacco prevalence in South Africa. Workplace health promotion, however, is not well established in many workplaces. This study aimed to develop, implement and evaluate the effectiveness of a culturallysensitive and contextually-appropriate collaborative workplace health promotion literacy programme on tobacco use, utilizing tailored health information leaflets and the Rhodes University peer educators support staff, guided by the World Health Organization Workplace Health Promotion Framework. Method: The research was conducted using a participatory action research approach, which involved four phases: Firstly, the Exploratory phase assessed tobacco-related health promotion policies and practices at Rhodes University; and established facilitating and constraining factors related to tobacco use. Secondly, the Educational health promotion phase involved designing and testing a health promotion educational intervention to address tobacco use related challenges, which took the form of culturally sensitive and appropriate health information leaflets to be used as an educational intervention Thirdly, in the Implementation phase health promotion training workshops were conducted with volunteering Rhodes University Peer Educators. Finally, an Evaluation phase involved evaluating the tobacco health promotion programme presented to the Rhodes University Peer Educators through a focus group discussion; and evaluating Peer Educator recall on the tobacco related health information discussed during the training workshops through a post-post intervention questionnaire. Eight semi-structured interviews (SSIs) and seven focus group discussions (FGDs) were conducted with support staff, peer educators and key stakeholders to establish the need for a comprehensive workplace health promotion initiative, and to identify the facilitating and constraining factors to conducting such an initiative on tobacco use at the University. Three health information leaflets (HILs) were developed collaboratively with the Peer Educators following a series of scientific, end-user testing approaches. The HILs were tested for readability, comprehension, actionability and suitability. A four-day health promotion training programme was conducted to improve user friendliness, memory retention and recall of the HILs by the peer educators and to improve tobacco related health literacy aspects. The participants' memory recall was evaluated using a pre- and post-, and post-post-intervention questionnaire to evaluate knowledge transfer. The study participants were also equipped with the completed HILs to distribute to their peers and to use as reference sources of information when needed in future. Results: The peer educators and institutional management supported the need for a tobacco workplace health promotion intervention. The intervention and evaluation phase of this study proved that health information material developed was readable, actionable, suitable, userfriendly, culturally sensitive and contextually appropriate. The workshops resulted in a significant increase in the participants' tobacco related health knowledge. Through the adoption of a collaborative approach to the research, the participants felt empowered and ready to be agents of change amongst their peers in the workplace. Recommendations: The collective use of external expert reviewers, end-user testing techniques and validated computer programmes are recommended to improve the validity of health promotion research outcomes. A longitudinal study that focus on behaviour change, specifically, with health evaluation and monitoring aspects could be conducted as the next step to this study.
Keywords: Tobacco use -- Health aspects; Smoking -- Health aspects; Employee health promotion; Employee health promotion -- Computer programs; Rhodes University -- Employees -- Tobacco use